Desain Perbaikan Proses Customs Clearance Menggunakan Value Stream Mapping, Critical Path Method dan Benchmarking - iqbal Firmansyah (Business Journal : Jurnal Bisnis Dan Sosial, 2022)
This research aims to develop a methodology for applying the principles of lean manufacturing in the service industry Courier Express. Customs is the main process in the industry express courier and the objective here is to apply lean principles to eliminate processes that have no added value and common parameters between the processes and optimization of resources humans or the allocation of workers. Value Stream Mapping (VSM) is used to identify a variety of waste on the current conditions and the Critical Path Method (CPM) identify the critical path in the process that takes place at this time. Model simulation of the Current Value Stream Mapping and Future State Mapping developed by using lean principles in the model simulation. The design of the repair process scheduling is done by analyzing the critical path process of Customs Clearance, with a critical path analysis we can determine the most process priority and most influential against the thorough repairs. A fusion method of Value stream mapping and Cricital Path Method supported by the method of benchmarking to finding best practice that has been done in the industry and doing the improvement so that the simulation generate a future state map with with the new critical path with faster acceleration time of customs clearance process from a total of 936 minutes before improvement and only required 389.6 minutes after improvements.